2023
DOI: 10.3390/nu15163588
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome, Epigenome, and Diet in Adults with Obesity during Behavioral Weight Loss

Abstract: Obesity has been linked to the gut microbiome, epigenome, and diet, yet these factors have not been studied together during obesity treatment. Our objective was to evaluate associations among gut microbiota (MB), DNA methylation (DNAme), and diet prior to and during a behavioral weight loss intervention. Adults (n = 47, age 40.9 ± 9.7 years, body mass index (BMI) 33.5 ± 4.5 kg/m2, 77% female) with data collected at baseline (BL) and 3 months (3 m) were included. Fecal MB was assessed via 16S sequencing and who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Differences in gut microbiota composition can impact nutrient absorption, gut barrier function, inflammation, and interactions with other organ systems ( 70 ). Furthermore, the metabolic pathways, whether involved in short-chain fatty acid production, amino acid metabolism, or other processes, might hold the key to understanding how gut microbiota influence weight and overall health ( 71 73 ). Using the full-length method, 35 differentiated metabolic pathways were identified, whereas the V3–V4 region method revealed 28 differentiated metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in gut microbiota composition can impact nutrient absorption, gut barrier function, inflammation, and interactions with other organ systems ( 70 ). Furthermore, the metabolic pathways, whether involved in short-chain fatty acid production, amino acid metabolism, or other processes, might hold the key to understanding how gut microbiota influence weight and overall health ( 71 73 ). Using the full-length method, 35 differentiated metabolic pathways were identified, whereas the V3–V4 region method revealed 28 differentiated metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Akkermansia muciniphila, another SCFA producer and mucindegrading bacterium, increased during different restriction programmes in five clinical trials [23,92,97,106,116]. As the level of A. muciniphila is inversely correlated with body weight and directly correlated with the weight loss observed in obese patients after CR restrictions and improvements in multiple indicators of cardio-metabolic health [128][129][130][131], it can be proposed as a prognostic tool in the context of predicting CR success. Further studies are needed to confirm this, as the effect was not consistently observed in all trials.…”
Section: The Impact Of Cr Programs On the Gut Microbiota-common Findingsmentioning
confidence: 99%